STRATEGI EFEKTIF DALAM PENANGANAN KEMBALI PRODUK DAN PENARIKAN KEMBALI PRODUK UNTUK MENJAMIN KUALITAS DAN KEPUASAN KONSUMEN - Nadia Safitri; Siti Noorlena (Jurnal Riset Multidisiplin Edukasi, 2025)
Product recall is a crucial step taken by companies to protect consumers from defective or hazardous products. An effective product recall strategy can maintain product quality and enhance consumer satisfaction, which in turn contributes to brand reputation and trust. This article aims to develop an effective product recall strategy through case study analysis of companies that have implemented product recalls. The research employs a descriptive qualitative approach with data collection techniques including interviews with quality managers, literature review, and secondary data analysis. The data analysis techniques used are thematic analysis and SWOT analysis to evaluate the strategies and their impact on product quality and consumer satisfaction.